The role of different transportation in the spreading of new pandemic influenza in mainland China - Zhang, Yun; Zhang, Yong; Liu, Zhigang (2011 19th International Conference on Geoinformatics, 2011)
In March 2009, influenza A(H1N1) was first detected in Mexico, and quickly spread to other countries. Civil aviation traffic played a very important role during the global spread of the epidemic. We build a spatial-temporal model to simulate the spreading process of influenza A(H1N1) at two spatial scales: simulating case evolution within province and inter-provincial spread in mainland China. Using inter-provincial passenger traffic data of railway, civil aviation and highway transportation, we calculate the daily probability of mobility of individuals between the 31 provinces by different transportation routes and analyze the effect of these three forms of transport upon travel between provinces. Simulation experiments about spreading process of pandemic influenza A(H1N1) have been done with different probability data. According to these simulation data, we evaluate the influence on the spatial distribution of cases at the national scale caused by different modes of transportation.